Allele frequencies for 15 short tandem repeat loci in representative sample of Croatian population - Projić, Petar; Škaro, Vedrana; Šamija, Ivana; Pojskic, Naris; Durmić-Pašić, Adaleta; Kovačević, Lejla; Bakal, Narcisa; Primorac, Dragan; Marjanović, Damir (2007)
Summary: Aim:To study the distribution of allele frequencies of 15 short tandem repeat (STR) loci in a representative sample of Croatian population. Methods: A total of 195 unrelated Caucasian individuals born in Croatia, from 14 counties and the City of Zagreb, were sampled for the analysis. All the tested individuals were voluntary donors.Buccal swab was used as the DNA source. AmpFlSTR® Identifiler® was applied to simultaneously amplify 15 STR loci.Total reaction volume was 12.5 μL. The PCR amplification was carried out in PE Gene Amp PCR System Thermal Cycler.Electrophoresis of the amplification products was preformed on an ABI PRISM 3130 Genetic Analyzer.After PCR amplification and separation by electrophoresis, raw data were compiled, analyzed, and numerical allele designations of the profiles were obtained.Deviation from Hardy-Weinberg equilibrium, observed and expected heterozygosity, power of discrimination, and power of exclusion were calculated.Bonferroni's correction was used before each comparative analysis.Results: We compared Croatian data with those obtained from geographically neighboring European populations.The significant difference (at P<0.01) in allele frequencies was recorded only between Croatian and Slovenian populations for vWA locus.There was no significant deviation from Hardy-Weinberg equilibrium for all the observed loci. Conclusion: Obtained population data concurred with the expected "STR data frame" for this part of Europe
Bibliografija: 23 jed
Keywords: Genetski parametri -- Aleli -- Frekvencija alela -- Kratki ponavljajući slijedovi -- Hrvatska populacija